The Influence of Influencer Marketing and Online Customer Reviews on Purchase Decisions with Mediator Brand Image - Mustajab, Fuad; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2025)
This study aims to analyze the influence of influencer marketing and online customer reviews on purchase decisions by examining the mediating role of brand image in the context of the TikTok social commerce platform. The novelty of this study lies in the integration of these three variables into a single relationship model on TikTok Shop, which is characterized by video content. This study used a quantitative approach with a purposive sampling method, involving 126 respondents in the Greater Jakarta area who were active users and had made purchases on TikTok Shop. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that influencer marketing and online customer reviews have a positive and significant influence on purchase decisions and brand image. Furthermore, brand image also significantly influences purchase decisions and mediates the relationship between influencer marketing and online customer reviews. These findings indicate that marketing strategies through influencers and customer reviews not only have a direct influence on purchase decisions but also an indirect influence through brand image formation. A strong brand image plays a crucial role in encouraging consumers to make purchase decisions on TikTok Shop.